Analysis of calcium concentration in perimenopausal women hair - Wlaźlak, Edyta; Surkont, Grzegorz; Dunicz-Sokołowska, Aldona; Długaszek, Maria; Radomska, Krystyna; Stetkiewicz, Tomasz; Graczyk, Alfreda (Menopause Review/Przegląd Menopauzalny, 2007)
Analysis of concentrations of bioelements in hair seems to be a promising method of initial diagnostics. Aim of the study: The aim of the study was to define calcium concentration in hair of perimenopausal women. Material and methods: In this paper we analyzed the results of calcium concentration in 258 Polish women aged 42-58. Results: Median analysis confirmed that between years 48 and 49 of life there was a statistically significant change of calcium accumulation in hair. After the age of 49 there took place a strong drop in calcium concentration in hair; all medians are found under the regression curve. Conclusions: Calcium concentration in the hair of the examined group of women lowered as a function of age. The drop started at the age of 49.